Trust and reciprocity in youth labor markets: An experimental approach to analyzing the impact of labour market experiences on young people - Shane Niall O'Higgins; Marco Stimolo (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2019)
In this experiment, we study whether individuals' labour market state (i.e. employed, student or NEET) affect their trusting and trustworthy behavior. To identify both the effect of labour market state and the effect of information on others' labour market state over one's behavior, we implement an experiment with two one-shot trust games with random and anonymous matching: in the first game, subjects receive no information on the counterpart; in the second one, the labour market state of both players is common knowledge. We find that, amongst the different sub-categories of NEETs, the status of unemployed has a markedly negative effect on trust and trustworthiness. Furthermore, precariousness in the labour market results to be as damaging as unemployment for trust and trustworthiness.
Keywords: C91; D31; D90; 330; Trust game; Reciprocity; Youth labor market